Multi-ratio optical thermometry and energy storage characteristics of Yb3+/Er3+/Tm3+ doped BaNb2O6 transparent glass-ceramics. (1st March 2023) - Xing, Junhao; Luo, Feng; Qin, Yaoyi; Chen, Xiaolu; Liang, Yingying; Gao, Zhixin; Shang, Fei; Xu, Huarui; Chen, Guohua
Highlights: RE-doped BaNb2 O6 transparent glass ceramics (GCs) were fabricated firstly. Realizing three-mode Up-conversion optical thermometry in the GCs. The maximum S r-max and S a-max can reach 2.30% K –1 and 6.71‰ K –1 . Achieving high W d of 0.99 J cm –3 and high P d of 225.3 MW cm –3 . Multifunctional GCs can be used in optical sensing and energy storage fields. Abstract: In order to meet the needs of new materials gradually developing towards miniaturization, integration, and light weight, multifunctional BaNb2 O6 : Yb 3+ /Er 3+ /Tm 3+ transparent glass-ceramics were successfully prepared by melt quenching and controllable crystallization. Its structure, luminescence, and energy transmission were studied. Using the opposite temperature dependence of the Tm 3+ emission band and the corresponding large energy level gap, a maximum relative sensitivity of 2.3% K –1 based on thermal coupling levels (TCLs) is obtained in a wide temperature range (298–673 K). The multi-ratio optical thermometry based on TCLs and non-TCLs is successfully realized by using the different emission bands of double emission centers, which makes it possible for self-reference optical temperature measurement modes. In addition, the transparent glass-ceramic exhibits excellent electrical properties under 700 kV cm –1 electric field: high discharge energy density ( W d  = 0.99 J cm –3 ), huge instantaneous power density (225.3 MW cm –3 ), and ultra-fast discharge rate ( T 0.9 ≤ 15.8 ns). The prepared glass-ceramic is expected to be a new type of lead-free multifunctional photoelectric material for temperature sensors and transparent electronic devices.